José Watanabe y Carlos López Degregori: de las metáforas ontológicas a las orientacionales - Fernández Cozman, Camilo Rubén (2022)
José Watanabe and Carlos López Degregori are two great Peruvian poets of the seventies of the last century. The article places the two authors in the field of Peruvian literary tradition. In Watanabe poetry, ontological metaphors predominate; on the contrary, in López's, the orientational metaphors prevail. The analysis is based on the ideas of George Lakoff and Mark Johnson to examine these metaphorical procedures and suggest that there is the functioning of the critical consciousness of the modern poet in Watanabe's work. In addition, the author studies the spatialization of the subject in López's poetry.